Comprehensive Natural Products III : chemistry and biology - Begley, Tadhg P.; Liu, Hung-wen, 1952- (Elsevier, 2020)
"Comprehensive Natural Products III, Third Edition, updates and complements the previous two editions, including recent advances in cofactor chemistry, structural diversity of natural products and secondary metabolites, enzymes and enzyme mechanisms and new bioinformatics tools. Natural products research is a dynamic discipline at the intersection of chemistry and biology concerned with isolation, identification, structure elucidation, and chemical characteristics of naturally occurring compounds such as pheromones, carbohydrates, nucleic acids and enzymes. This book reviews the accumulated efforts of chemical and biological research to understand living organisms and their distinctive effects on health and medicine and to stimulate new ideas among the established natural products community."